2019
DOI: 10.21873/anticanres.13166
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Toll-like Receptor 4 Is Associated With Poor Prognosis in Bladder Cancer

Abstract: Background/Aim: The aim of this study was to elucidate the relationship between the progression of bladder cancer (BCa) and TLR4 expression. Materials and Methods: The relationship between TLR4 expression and prognosis of BCa patients was analyzed using a publicly available database and immunohistochemical staining of clinical samples. The effect of TLR4 knockdown was also examined on the invasive capabilities of BCa cells. Finally, to investigate the biological function of TLR4, the gene expression profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
0
1
Order By: Relevance
“…A low level of TLR4 can effectively forecast poor outcomes for bladder cancer patients. The result is consistent with a previous report (Kusuhara et al, 2019). Moreover, the expression of TLR4 is lower in the elderly, high grade tumors, higher tumor stage, and progressive tumors.…”
Section: Discussionsupporting
confidence: 93%
“…A low level of TLR4 can effectively forecast poor outcomes for bladder cancer patients. The result is consistent with a previous report (Kusuhara et al, 2019). Moreover, the expression of TLR4 is lower in the elderly, high grade tumors, higher tumor stage, and progressive tumors.…”
Section: Discussionsupporting
confidence: 93%
“…In the future, we will have to experiment with other more accurate method such as 3D to investigate the status of invasion. In this study, we could not show the evidence to suggest which downstream signal pathways including growth factors and cytokines such as previously reported (47,48) are involved in cell proliferation, invasiveness, and so on.…”
Section: Discussioncontrasting
confidence: 86%
“…On the other hand, the manipulation with these molecules might present an opportunity for the therapeutic impact onto the disease course. Kusuhara et al [9] arrived at a conclusion that lower expression of TLR4 correlates with poor prognosis of BC, with squamous differentiation of MIBC, lower cell proliferation, but higher invasiveness of cancer cells; depletion of TLR4 in low-stage BC cell lines increased the expression of cell morphology related genes, including keratin proteins and small proline-rich proteins. In our study, we found that in all BC cases tumor tissue had lower expression of TLR4 as compared to the unaffected portions of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Among TLRs the expression of TLR type 4 (TLR4) turned out to be the most prominent and relevant to the progression of BC and its prognosis [9]. TLR4 is present both on immune cells and BC cells [10], which makes it difficult to distinguish the dual role of TLR4 in cancer progression and anticancer immunity [11,12].…”
mentioning
confidence: 99%